CPW-Fed Dual Band Flexible Antenna for Energy IoT Applications at 380/940 MHz - Lee, Soyeong; Do, Sangjoon; Lee, Hoosung; Yoon, Daeyeong; Park, Yong Bae (IEEE Access, 2025)
In this paper, we present the design and fabrication of a dual-band flexible antenna for energy Internet of Things (IoT) applications operating at 380 MHz and 940 MHz. The antenna features a coplanar waveguide (CPW) feed structure and a T-shaped monopole design on a polyimide substrate, with tapered stepped ground plane and square ring-shaped parasitic elements to minimize performance degradation due to bending. The antenna size is 210× 236× 0.2 mm3, achieving bandwidths of 25.2% (344∼ 440 MHz) and 15.2% (863∼ 1006 MHz) when flat, with peak gains of 2.52 dBi and 4.90 dBi, respectively. We evaluate the antenna's performance under various bending conditions using cylindrical styrofoam structures with radii of 25, 35, 45 cm, and the bandwidth degradation is within 4%. To verify the realistic applicability in energy IoT applications, we perform performance analysis considering a transmission tower environment with a cylindrical metal structure having a diameter of 60 cm, ensuring that performance degradation is minimized at a distance of at least 5 cm from the metal structure. Link margin calculations for Korea Electric Power Corporation (KEPCO)'s IoT specifications demonstrate values of 34.08 dB at 380 MHz and 31.94 dB at 940 MHz, confirming the antenna's suitability for KEPCO's energy IoT applications. These results indicate that the proposed antenna meets the requirements for efficient operation in KEPCO's IoT infrastructure.
Keywords: Co planar waveguide feed (CPW); Dual Band; Energy internet; Energy internet of thing; Feed structure; Flexible antennas; Metal structures; Parasitic element; Performance degradation; Tapered stepped ground; Energy IoT; flexible antenna; parasitic element; tapered stepped ground